2005
DOI: 10.1592/phco.2005.25.12.1725
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Dose Vitamin C on Hepatic Cytochrome P450 3A4 Activity

Abstract: Sex and baseline CYP3A4 activity appeared to influence the effect of vitamin C on CYP3A4 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In addition to smoking, some dietary chemicals may regulate the catalytic activity of CYPs. For example, an increase of unsaturated fatty acids in food can enhance the expression of CYPs in the liver [ 80 ], and lacking protein, vitamin C, calcium, or magnesium in food may reduce the activity of CYPs in the process of metabolizing some drugs [ 81 , 82 , 83 ]. CYP3A can be induced by some brassicaceous vegetable, such as turnips and spinach, causing the enhancement of the first-pass effect of phenacetin [ 84 ].…”
Section: Individual Variation Of Cyp-mediated Drug Metabolismmentioning
confidence: 99%
“…In addition to smoking, some dietary chemicals may regulate the catalytic activity of CYPs. For example, an increase of unsaturated fatty acids in food can enhance the expression of CYPs in the liver [ 80 ], and lacking protein, vitamin C, calcium, or magnesium in food may reduce the activity of CYPs in the process of metabolizing some drugs [ 81 , 82 , 83 ]. CYP3A can be induced by some brassicaceous vegetable, such as turnips and spinach, causing the enhancement of the first-pass effect of phenacetin [ 84 ].…”
Section: Individual Variation Of Cyp-mediated Drug Metabolismmentioning
confidence: 99%
“…The different activities depend on the dosage used [89]. Vitamin C is a CYP inhibitor in vitro [90]. Similarly, quercetin has been shown to have the same activity of CYP inhibition [91].…”
Section: Pro-oxidant Activity Of Nutraceuticalsmentioning
confidence: 99%
“…A clinical study showed that vitamin C reduced plasma concentrations of a protease inhibitor (Slain et al, 2005), suggesting that vitamin C might affect CYP3A4‐activity. A modest induction of CYP3A was found when giving a high dose of vitamin C (500 mg twice/day), but the effect was only seen in male subjects (Van Heeswijk et al, 2005).…”
Section: Resultsmentioning
confidence: 99%